MENGENAL DAN MENERAPKAN ECOMMERCE UNTUK MENGAMBIL PELUANG USAHA UNTUK GENERASI MUDA DI SMK BISTEK CIBINONG - Diki Rasapta; Syndhe Qumaruw; Septa Septa (Abdi Jurnal Publikasi, 2022)
Of all aspects of life affected by the growth of the internet, the business sector is the sector most affected by the development of information and telecommunications technology and the fastest. Now emerging transactions using internet media that connect producers and consumers. Through e-commerce, all humans on earth have the same opportunities and opportunities to compete and succeed in doing business in cyberspace. With the rapid development of e-commerce around the world, online customer segmentation is attracting the attention of business people and academics. The development of online business in Indonesia cannot be separated from the development of cellular and internet users in the last five years. On the other hand, the government continues to encourage cellular operators and internet providers to reduce all transaction fees charged to consumers. So that online business becomes the choice of modern entrepreneurs. E-commerce is usually carried out by business people through websites (sites). The widespread use of websites is closely related to its superiority in conveying information that is not limited by space and time. Through online shopping sites, shopping patterns in people's lives, especially people who are active in using the internet, are now experiencing significant changes. With the internet, consumers no longer need to go directly to the place of shopping, but simply access the sites of online buying and selling providers. In addition, in conducting transactions the buyer can transfer funds to the seller. Not only direct transfers, in order to maintain the security of buyers, they can also use third parties or joint accounts provided by online buying and selling owners [1].